1998
DOI: 10.1116/1.580992
|View full text |Cite
|
Sign up to set email alerts
|

C 2 column densities in H2/Ar/CH4 microwave plasmas

Abstract: We report the observation of the d 3Πg→a 3Πu Swan bands of the C2 molecule both in absorption and emission in a H2/Ar/CH4 microwave discharge plasma. The input mole fraction of methane is varied from 1% to 33%. From the observed absorptions, we calculate the column density of gas phase C2. The calculated concentration of C2 is higher in discharges containing large fractions of argon than in discharges containing large fractions of hydrogen. These observations are useful in understanding the contribution of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…12 Previous studies 13,14 explored initial growth stages with dicarbon on the hydrogen-terminated ͑110͒ face without hydrogen abstraction by way of insertion of C 2 into C-H bonds on the surface. The presence of C 2 near the surface during growth and its likely contribution to the growth process have been confirmed experimentally through characteristic intense Swan-band radiation in both microwave plasma chemical vapor deposition 4,5 and hot-filament chemical vapor deposition. 6 In the present work, we consider deposition steps onto the clean diamond ͑110͒ surface without hydrogen participation.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…12 Previous studies 13,14 explored initial growth stages with dicarbon on the hydrogen-terminated ͑110͒ face without hydrogen abstraction by way of insertion of C 2 into C-H bonds on the surface. The presence of C 2 near the surface during growth and its likely contribution to the growth process have been confirmed experimentally through characteristic intense Swan-band radiation in both microwave plasma chemical vapor deposition 4,5 and hot-filament chemical vapor deposition. 6 In the present work, we consider deposition steps onto the clean diamond ͑110͒ surface without hydrogen participation.…”
Section: Introductionmentioning
confidence: 84%
“…Conventional diamond films as grown from H/CH 3 mixtures are characterized by crystallites in the micrometer size range. In several recent experiments [4][5][6] it was confirmed that the addition of argon to the plasma allows continuous control over the crystallite size. Most importantly, at argon concentrations in a narrow window around 95%, the resulting films are ultrananocrystalline with a typical crystallite size of just 3-10 nm.…”
Section: Introductionmentioning
confidence: 99%
“…33,38,50,70,88 C 2 radical density of 10 11 to 10 13 cm À3 was demonstrated in the MW and ICP systems employing a CH 4 /H 2 or CH 4 /H 2 /Ar mixture. [114][115][116] Teii et al conducted plasma diagnosis and material characterization on a TM-MW plasma (employing C 2 H 2 /N 2 /Ar or CH 4 /N 2 /Ar) as well as the as-grown deposits. 33 As shown in Fig.…”
Section: Carbon Sourcesmentioning
confidence: 99%
“…Three years ago we reported observing the C 2 radical using absorption spectroscopy in a microwave plasma similar to that used to grow the nanometer scale polycrystalline films 1 . This work was performed in our own laboratory at the Univ.…”
Section: Subject Termsmentioning
confidence: 99%